DIGITAL TRANSFORMATION OF THE BUSINESS PROCESS MANAGEMENT SYSTEM AT ENTERPRISES UNDER CONDITIONS OF INSTABILITY - KOSIIUK, Olena; RIEPIN, Mykyta (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the issues of digital transformation of business process management systems at enterprises operating under conditions of an unstable external environment. It is substantiated that increasing economic, technological, and regulatory instability complicates the coordination of business processes, increases managerial risks, and reduces the effectiveness of traditional management approaches. It is determined that fragmented implementation of digital technologies without their integration into a unified management system does not provide a systemic effect and limits the adaptability of enterprises.The purpose of the study is to provide a theoretical and methodological substantiation of approaches to the digital transformation of business process management systems under unstable conditions and to develop a holistic model aimed at increasing flexibility, coherence, and effectiveness of managerial decisions. The research summarizes modern scientific approaches to digital transformation of management, systematizes the main directions of business process digitalization, and identifies the role of information and analytical support in managerial decision-making.A model of digital transformation of the business process management system is proposed, integrating the impact of the unstable external environment, management functions, business processes, and digital technologies within a unified management logic. Special attention is paid to the feedback mechanism, which ensures continuous adjustment of managerial decisions in accordance with changes in external conditions and the performance results of business processes. The proposed model enables a transition from fragmented and reactive management to integrated, data-driven management, enhancing transparency, reducing management cycles, and increasing organizational adaptability.The practical implementation of the proposed model creates prerequisites for improving manageability, flexibility, and sustainability of enterprise operations in conditions of external instability, contributing to more effective use of digital technologies and improved coordination of business processes.
Keywords: digitalization; digital transformation; development; business processes; management system; digital technologies; managerial decisions; unstable external environment; adaptability; management efficiency